Designing Promotional Video for Buwun Sejati Tourism Village as a Tourism Promotion Media - Rizki Meli Lestari; M Tanggap Sasmita; Sri Wahyuni (J-TRUE: Journal of Travel and Leisure, 2024)
One of the currently developing tourism trends is tourism villages, this is inseparable from tourism promotions carried out to influence tourists to visit a destination. Buwun Sejati Tourism Village is one of the villages in Narmada District, West Lombok Regency. The level of visits by domestic tourists has increased, but visits by foreign tourists are still relatively low. This study aims to identify tourism potential and design a promotional video for Buwun Sejati Tourism Village to attract foreign tourists. This study uses a qualitative research methodology with data collection through participant observation, interviews, and literature study. The result of this study is that Buwun Sejati Tourism Village has many diverse tourist objects as well as interesting tourist attractions to visit which can be used as an attraction to attract visiting tourists. The final artwork from the video design process resulted in the final two-day and one-night tourism village promotion video Explore Buwun Sejati Tourism Village with a duration of two minutes and 40 seconds in mp4 format.